Nutritional education of the mother and its relationship to the phenomena of children's growth (Journal of the College of Basic Education, 2023)
The research aims to identify the nutritional education of mothers (teachers in secondary schoolsand middle school) and its relationship to some aspects of her child's growth represented in weight, height, family size,Eleven null hypotheses were formulated, and the research was limited to (200) schools (mother) with(200) children ranging in age from (1-5) years, and the researcher has prepared a measure of educationThe nutritional value was characterized by honesty and stability, through which the nutritional education of the school sample was measured.In addition to measuring (the weight, height and size of the family) of the children of the research sample and comparing that withThe global mean for each of the measured growth parameters.Among the most prominent results of the research, there are no statistically significant differences at the level of significance (0.05).There is a difference in the weight of the children, and there is a difference in the height and the size of the families for the children of the specialized teachers.scientific, and the correlation coefficient is weak between the nutritional education of female teachers and the manifestations of growththeir children. As for the most prominent recommendations and suggestions: -- The need to seriously consider the nutritional education of mothers.Continuous measurement, and interest in children's integrated food (quantity and quality) and in a mannerScientific.- A study of the mother's nutritional education (school) and its relationship to other developmental aspects such as the farmer's environment.chest circumference, children's intelligence, and a study of nutritional education for city schools.And the countryside, and female and female teachers.